Vengeance : the true story of an Israeli counter-terrorist team - Jonas, George, 1935-2016 (New York : Simon and Schuster, 1984)
"Vengeance is a story that reads like a novel. It is the account of five ordinary young Israelis, selected to vanish into "the cold" of espionage secrecy - their mission to hunt down and kill the PLO terrorists responsible for planning the massacre of eleven Israeli athletes at the Munich Olympics in 1972"--Inside jacket.
Includes bibliographical references (pages 375-376)
Keywords: Jewish-Arab relations; Counterinsurgency -- Israel; Jewish-Arab relations; Terrorismus; Israel